Apek Hukum Pemanfaatan Tanah Kas Desa Untuk Pembangunan (Studi Di Desa Mulyoagung Kecamatan Dau Kabupaten Malang) - jumi arianti (Fakultas Hukum Universitas Islam Malang, 2020)
The purpose of this study was to determine the implementation of the management and utilization of the village treasury as an allowance for village officials against the applicable regulations. To find out the implementation and management of village treasury land by village officials to tha community. Management and ututilization of village treasury land in Indonesia must be based on the principles that have been regulated in the applicable laws and regulations, namely, the principle of public interest, funtional principle, principle of legal certainty, principle of transparency, principle of effectiveness, principle of accountability, principle of value assurance and economy. Village treasury land is used for agricultural land, village markets, paud schools, buildings, cafes and TPST (integrated waste collection facilities)Keywords:legal Aspects, Utilization, Village Treasury LandABSTRAK Tujuan penelitian ini adalah untuk mengetahui pelaksanaan pengelolaan dan pemanfaatan tanah kas desa sebagai tunjangan untuk perangkat desa terhadap peraturan yang berlaku. Untuk mengetahui pelaksanaan pengelolaan dan pemanfaatan tanah kas desa oleh perangkat desa kepada masyarakat. Pengelolaan dan pemanfaatan tanah kas desa di Indonesia harus berdasarkan pada asas-asas yang telah diatur dalam peraturan perundang-undangan yang berlaku yaitu asas kepentingan umum, asas fungsional, asas kepastian hukum, asas keterbukaan, asas efektivitas, asas akuntabilitas, asas kepastian nilai dan ekonomi. Tanah kas desa dimanfaatan untuk lahan pertanian, pasar desa, sekolah paud, gedung, cafe dan TPST (tempat penampungan sampah terpadu.Kata Kunci: Aspek Hukum, Pemanfaatan, Tanah Kas Desa.